Kajian Kualitas Air Sungai pada Kali Mas Kota Surabaya - Hasna Aqilah Putri Agdy; Okik Hendriyanto Cahyonugroho (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The objective of this research is to assess the water quality of the Kali Mas River in Surabaya by focusing on its chemical, physical, and biological attributes. A quantitative descriptive approach was used, with sampling taken at four points along the river. The results of this analysis refer to the quality standards set in Government Regulation No. 22 of 2021. The observed parameters include pH, TSS (Total Suspended Solids), DO (Dissolved Oxygen), phosphate, COD (Chemical Oxygen Demand), BOD (Biochemical Oxygen Demand), nitrate, and fecal coliform. Based on the Water Quality Index calculation, the water quality of Kali Mas is categorized as moderate. However, some parameters such as BOD, COD, and phosphate indicate light pollution. This study highlights the importance of sustainable pollution management and control to maintain ecosystems and support community needs.